Historiografi Alur Islamisasi Ponorogo: dari Ki Ageng Mirah hingga Pesantren Gebang Tinatar Tegalsari: Historiography of Islamization in Ponorogo:from Ki Ageng Mirah to Pesantren Gebang Tinatar Tegalsari - Muh Ashif Fuadi (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2023)
This research explains the historiographical flow of the Islamic da'wah inPonorogo from the time of Kiai Ageng Mirah until the formation of theIslamic boarding school network in Ponorogo. This research uses a literaturestudy method with a historical approach. The research resulted in theconclusion that: first, the historiographical flow of the spread of Islam in thePonorogo region is divided into four stages, the initial phase, namely the late1400s to 1500s, which was played by Kiai Ageng Mirah, one of SunanKalijogo's pupil, the 1600s phase of Islamic propagation in Ponorogo whichwas played by Kiai Donopuro, one of the descendants of Sunan Bayat, the1700 phase during the time of Kiai Ageng Muhammad Besari, a pupil of Kiai Donopuro, the 1800 phase played by Laskar Diponegoro after the end of theJava War, and the 1900 phase when Islamic boarding schools emerged. Second, continuously from the initial phase from 1500 to 1900, the da'wahmovement developed by these figures inherited the scientific style of theWalisongo tradition, characteristic of Indonesian Islam. Third, specifically, the Islamic boarding school network that was formed after 1900 in thePonorogo area are Islamic boarding schools that are still closely related to thePesantren Tegalsari and the descendants of Laskar Diponegoro bothgenealogically and ideologically. Penelitian ini menjelaskan tentang alur historiografi masuknya dakwah Islam diwilayah Ponorogo dari masa Kiai Ageng Mirah sampai terbentuknya jaringanpesantren di Ponorogo. Penelitian ini menggunakan metode studi pustaka denganpendekatan historis. Penelitian menghasilkan kesimpulan bahwa: pertama, alurhistoriografi penyebaran Islam di wilayah ponorogo terbagi menjadi empat tahapan,fase awal yakni tahun tahun 1400 akhir sampai 1500 yang diperankan oleh KiaiAgeng Mirah salah seorang murid dari Sunan Kalijogo, fase tahun 1600 dakwahIslam di Ponorogo yang diperankan oleh Kiai Donopuro salah seorang keturunandari Sunan Bayat, fase tahun 1700 pada masa Kiai Ageng Muhammad Besari muriddari Kiai Donopuro, fase tahun 1800 yang diperankan oleh Laskar Diponegoro pascaberakhirnya Perang Jawa, dan fase tahun 1900 muncul pesantren-pesantren. Kedua, secara berkesinambungan dari fase awal tahun 1500 sampai 1900 gerakan dakwahyang dikembangkan oleh tokoh-tokoh tersebut mewarisi corak keilmuan tradisiWalisongo ciri khas Islam Nusantara. Ketiga, secara spesifik jaringan pesantrenyang terbentuk setelah tahun 1900 di wilayah Ponorogo merupakan pesantren yangmasih berhubungan keturunan dengan Pesantren Tegalsari dan keturunan LaskarDiponegoro baik secara genealogis maupun ideologis